2019
DOI: 10.1093/ptj/pzz183
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Cost-Effective Physical Therapy Approach (Coach2Move) to Improve Physical Activity in Community-Dwelling Older Adults With Mobility Problems: Protocol for a Cluster-Randomized, Stepped Wedge Trial

Abstract: Background Coach2Move is a personalized treatment strategy by physical therapists to elicit physical activity in community-dwelling older adults with mobility problems. Objective The primary objective of this study is to assess the effectiveness and cost-effectiveness of the implementation of Coach2Move compared with regular care physical therapy in daily clinical practice. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Developing information on how to adapt a protocol-based approach to accommodate shared decisions may be warranted with future work. 36 To operate as intended, POFs should be viewed as a patient-centered and participatory approach that could be applied in combination with the context of the patient's life and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Developing information on how to adapt a protocol-based approach to accommodate shared decisions may be warranted with future work. 36 To operate as intended, POFs should be viewed as a patient-centered and participatory approach that could be applied in combination with the context of the patient's life and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The LAPAQ is a scale created to determine the level of physical activity in older individuals. The LAPAQ is also frequently used in the literature (19,20). However, upon examining the LAPAQ version studies, the number of the studies conducted is observed to be limited (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Next, we specified determinants for adoption and implementation. Researchers at University of Utah Health performed a literature review identifying factors associated with clinician delivery of behavioral interventions (13,(24)(25)(26)(27). We met with Coach2Move developers to identify prior implementation experiences and contrasted this with the literature review.…”
Section: Matrices Of Changementioning
confidence: 99%
“…They also find it difficult to elicit motivation, address ambivalence, and partner with patients on strategies that change PA in everyday life ( 25 ). In Coach2Move, physical therapists train in motivational interviewing to engage patients in identifying meaningful goals, monitor progress, and plan for self-management through sustainable changes in PA ( 26 ). Coach2Move has demonstrated acceptability with patients and physical therapists, effectiveness in sustaining PA beyond an episode of physical therapy care, and cost-effectiveness ( 15 , 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%